The impact of the genie program on the integration of ICTs in Moroccan education and its effect on teachers - Dardary, Oussama; Elmazouni, Nourdine; Tridane, Malika; Belaaouad, Said (International Journal of Engineering and Technology, 2019)
This research focuses on the use and integration of ICTs (Information and Communication Technologies for Education) in Moroccan public schools, through a survey. A GENIE program was developed in September 2005 to improve the quality of teaching and learning. The main objectives of the GENIE strategy are: effective and rapid integration of ICTs into the education system; integration of ICTs at the heart of the learning process as a fundamental tool; positive interaction with educational programs; increase the quality of education through effective use of information technology by teachers and students; integration of multimedia and internet tools into educational methodologies and the learning process; qualification of future generations. Currently, we can say that we canâ€™t really notice the effects and the traces of this program. This study aims to describe the national project GENIE and its impact on the different educational actors.Â